Rancangan Alat Material Handling dengan Pendekatan Anthropometry Berdasarkan Perhitungan Recommended Weight Limit dan Lifting Index Pada PT. XYZ - Muhammad Faisal Yunia Hanafi; Efta Dhartikasari Priyana; Yanuar Pandu Negoro (Universitas Islam Raden Rahmat, Malang, 2024)
An important activity in a production process is material handling. One of the activities carried out at PT. Workers often complain of pain in the upper arms and shoulders. Therefore, an analysis of the Weight Limit and Lifting Index recommendations was carried out to determine the maximum weight that can be carried by workers. The calculation results show that the weight of the load lifted exceeds the recommended fattening limit because the LI value is> 1 and with a maximum RWL weight of 10.90 kg, so the worker's activities are at risk of spinal damage. Based on discussions with the company, material handling equipment in the form of a trolley is required. The dimensions of the proposed trolley are that the width of the trolley base is 35 cm; (b) The length of the trolley base is 80 cm; (c) The height of the trolley is 54.47 cm; (d) Trolley handle width 35.19 cm; (e) The height of the trolley handle is 95.16 cm